PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XII IPA 2 SMA NEGERI I BENGKALIS TAHUN PELAJARAN 2018/2019 - Faizah Hamid (STAIN Bengkalis, 2019)
This study aims to improve student mathematics learning outcomes through the cooperative learning model of the Numbered Heads Together (NHT) structural approach to the material Opportunities in Class XII IA 2 SMA Negeri 1 Bengkalis. This Classroom Action Research (CAR) was conducted in two cycles, each cycle consisting of 2 meetings. Each cycle consists of four stages, namely the stages of planning, implementation, observation, and reflection. The types of data collected in each cycle are qualitative and quantitative data, learning achievement tests, observation sheets and questionnaires. With the use of the NHT structural approach the classroom atmosphere becomes not monotonous, so students become more motivated, interested, and more active in participating in mathematics learning activities. In the first cycle, the percentage of students who have finished learning is 47.06%, while the percentage of student activity in learning activities is 65%. In the second cycle, the percentage of students who finished learning was 88.23% and the percentage of students' activeness in learning activities was 88%.Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika siswa melalui model pembelajaran kooperatif pendekatan struktural Numbered Heads Together (NHT) pada materi Peluang di Kelas XII IA 2 SMA Negeri 1 Bengkalis. Penelitian Tindakan Kelas (PTK) ini dilaksanakan dalam dua siklus yang masing-masing siklus terdiri dari 2 kali pertemuan. Masing-masing siklus terdiri dari empat tahap, yaitu tahap perencanaan, pelaksanaan, observasi, dan refleksi. Jenis data yang dikumpulkan pada setiap siklus berupa data kualitatif dan kuantitatif, tes hasil belajar, lembar observasi dan angket. Dengan penggunaan pendekatan struktural NHT suasana kelas menjadi lebih hidup dan tidak monoton, sehingga siswa menjadi lebih termotivasi, tertarik, dan lebih aktif untuk mengikuti kegiatan pembelajaran matematika. Pada siklus I, persentase siswa yang tuntas belajar sebesar 47,06%, sementara persentase keaktifan siswa dalam kegiatan pembelajaran sebesar 65%. Pada siklus II, persentase siswa yang tuntas belajar sebesar 88,23% dan persentase keaktifan siswa dalam kegiatan pembelajaran sebesar 88%._________________Keywords: Learning Model, Numbered Heads Together, Learning Outcomes.